Comparing the situation of FinTech start-ups in Russia and Germany through equity investments - Konstantin B. Kostin; Ralf Fendel; Friedrich Wild (Economies, 2022)
Examining and comparing the FinTech investment environments of major economies has untapped potential when it comes to comparing their innovativeness in the financial sector. Therefore, this paper examines the development of FinTech companies from Germany and Russia by investigating funding circumstances and by analyzing equity investments. The goal of the article is to analyze the growth and development of equity funding in FinTech companies in both countries. The underlying hypothesis for this investigation is the applicability of an exponential growth model for the examined funding rounds. The analysis shows that the German market has more FinTech start-ups pursuing equity funding rounds. From Pre-Seed to Series D funding, the considered investment market is about 18 times larger in Germany than it is in Russia. The German market shows strong evidence of exponentially increasing investment tickets based on the behavior of the total data set. This is further supported by testing exponential and linear models on the averages for the investment stages. In this analysis, the exponential model shows a significantly better fit than its linear counterpart. The analysis of the Russian market is not supportive of the hypothesis, as substantial evidence of the superiority of a linear model over an exponential model could be found. This, combined with comparatively compact average funding sizes, signals a more immature equity investment market in Russia.
Keywords: 330; equity investment; FinTech; start-ups